2003
DOI: 10.1046/j.1365-2788.2003.00488.x
|View full text |Cite
|
Sign up to set email alerts
|

Stress, social support and well‐being of Arab mothers of children with intellectual disability who are served by welfare services in northern Israel

Abstract: The findings are interpreted with respect to practice and previous studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 22 publications
1
42
0
2
Order By: Relevance
“…Similar stressful experiences were also reported by parents of children with autism [10] and intellectual disability [11,12]. Emotional experience of sadness, and inner pain or bitterness associated with having a mentally ill child differs from a previous study in the United States [9], where emotional strain was expressed by mothers as having fears, frustrations, and guilt in dealing with the child’s behaviour and attitude.…”
Section: Discussionsupporting
confidence: 56%
“…Similar stressful experiences were also reported by parents of children with autism [10] and intellectual disability [11,12]. Emotional experience of sadness, and inner pain or bitterness associated with having a mentally ill child differs from a previous study in the United States [9], where emotional strain was expressed by mothers as having fears, frustrations, and guilt in dealing with the child’s behaviour and attitude.…”
Section: Discussionsupporting
confidence: 56%
“…Duvdevany and Abboud (2003) noted that the higher the amount of the informal support resources available to mothers of children with ID in Saudi Arabia, the lower the level of stress and the higher the sense of well-being they experienced. Guralnick et al (2008) conducted a longitudinal study of 63 mothers, for which the results of multiple regression analyses revealed that parenting support during the early childhood period, irrespective of source, consistently predicted most dimensions of parental stress assessed during the early elementary years and contributed uniquely to the variance of outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…While a promising and growing scholarship examines the significance of intellectual disability on Arab families in northern Israel (Duvdevany and Abboud 2003;Reiter, Mari, and Rosenberg 1986), and the United Arab Emirates (Khamis 2007), to date no studies have considered the significance of intellectual disability to Bedouin-Arab families. As a corrective, the present article is the first to consider family members' experiences around intellectual disability amongst Bedouin-Arab communities in the Negev, Israel.…”
mentioning
confidence: 99%